(3QSGdI aj GdefWbs
(3ChdgG (B:s
(3dc aGfUQa LQFjkG JeGQV ai efRdg aYR Ydi Gdedc hhcd YhVg hHOG GdfGSc Cf jQLY aCNHQ GHf Gdedc Cf dg hdCUMGHg YgOkG bO MVQ abGd Cf CNQL eYc s
(3BNQgG (B:s
(3CNHQge Cf HYV gPG GdLhgQ bO VGY HjOi Cgd GdZOQ hGdNjGfI acSHhG Hg GdCehGd hLdhG Hg GdSagGA aefgG eG fWb hHUQ hSeY CeQge s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B19s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3JHUQGJ GdCUd (B:s
(3GdfSNI fGbUI GdChd , eHJhQI GdBNQ s
Keywords: (3GdadSaI hGdefWbs